MICROBIAL SURFACTANTS: CLASSIFICATIONS, PROPERTIES, RECOVERY, AND APPLICATIONS (Jurnal Teknologi (Sciences & Engineering), 2022)
Surface-active agents or surfactants are amphiphilic compounds derived naturally or chemically synthesized. Natural surfactants or so-called biosurfactants can be obtained from bacteria, yeasts, and fungi as well as plants. Due to their hydrophilic and hydrophobic molecules, biosurfactants offer the ability to reduce surface or interfacial tension and create microemulsion between aqueous and organic phases. Many studies have suggested biosurfactants as a better substitution to chemical surfactants since they are more environment friendly, biocompatible, and has lower toxicity. This review article is provided to introduce some general information regarding microbial-derived biosurfactants including five main classes of biosurfactants and several distinctive properties that confer them as promising surface-active agents. Due to their diverse molecular structures, biosurfactants have been applied in various applications. Thus, several common biosurfactant recovery methods are discussed and examples of biosurfactant applications in hydrocarbon removal as well as in industrial processing are highlighted.